Method for manufacturing a solar cell and solar cell
Patent Information
- Application Number
- CN202510426595.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]基于此,本申请提供一种太阳电池的制备方法及太阳电池,以解决现有技术中由于铜栅线底部出现贾凡尼效应导致的不利于提高栅线结合力的技术问题
[0025] The solar cell fabrication method and solar cell of this application embodiment involve a first chemical tin plating treatment performed at a relatively high temperature. This reduces the viscosity of the chemical tin plating solution, increasing its fluidity and allowing stannous ions to flow more easily to the bottom of the copper grid lines. Simultaneously, the first chemical tin plating treatment is performed in an ultrasonic environment, resulting in a more uniform distribution of stannous ions in the chemical tin plating solution. This further promotes the replenishment of stannous ions at the bottom of the copper grid lines, thus suppressing the galvanic effect at the bottom of the copper grid lines. The first chemical tin plating treatment uniformly covers the surface of the copper grid lines with a first tin plating layer. The second chemical tin plating treatment continues to form a second tin plating layer on top of the first tin plating layer. Since the surface of the copper grid lines is already covered with the first tin plating layer, copper oxidation caused by the galvanic effect will not occur during the second chemical tin plating process. This increases the contact area between the copper grid lines and the surface of the solar cell substrate, improves the grid line adhesion, and ultimately improves the product quality of the solar cell.
Smart Images

Figure CN122934944A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of photovoltaic technology, and in particular to a method for preparing a solar cell and the solar cell itself. Background Technology
[0002] In the fabrication process of solar cells, grid electrodes are prepared on a transparent conductive film using metal electroplating. First, a copper seed layer is formed on the transparent conductive film using PVD magnetron sputtering. Then, a photosensitive emulsion layer is coated on the copper seed layer. The grid pattern is printed on the photosensitive emulsion layer and exposed. Then, the part of the photosensitive emulsion layer with the grid pattern printed on it is removed by developing solution to form a groove on the photosensitive emulsion layer. Copper grid lines are then electroplated in the grooves and excess photosensitive emulsion layer is removed. Then, the solar cell is etched and cleaned using an etching solution to remove the copper seed layer. Finally, a tin protective layer is formed on the surface of the copper grid lines by chemical tin plating.
[0003] During the electroless tin plating process, due to the uneven distribution of stannous ions in the electroless tin plating solution, the content of stannous ions is relatively low at the bottom of the copper grid line. The galvanic effect is prone to occur at the bottom of the copper grid line, which leads to oxidation of the bottom of the copper grid line to form copper oxide. This reduces the contact area between the copper grid line and the solar cell substrate, which is not conducive to improving the grid line adhesion. Summary of the Invention
[0004] Based on this, this application provides a method for fabricating a solar cell and a solar cell to solve the technical problem in the prior art that the galvanic effect at the bottom of the copper grid line is detrimental to improving the grid line bonding force.
[0005] In a first aspect, one embodiment of this application provides a method for fabricating a solar cell, comprising:
[0006] A solar cell is provided, the solar cell including a solar cell substrate and copper grid lines disposed on the surface of the solar cell substrate;
[0007] The solar cell is subjected to a first chemical tin plating treatment in an ultrasonic environment to form a first tin plating layer on the surface of the copper grid lines;
[0008] The solar cell is subjected to a second chemical tin plating treatment to form a second tin plating layer on the surface of the first tin plating layer;
[0009] The temperature of the first chemical tin plating treatment is higher than the temperature of the second chemical tin plating treatment.
[0010] Optionally, the temperature of the first chemical tin plating treatment is 35℃~45℃, and the time of the first chemical tin plating treatment is 10s~30s.
[0011] Optionally, the temperature of the second chemical tin plating treatment is 30℃~40℃, and the time of the second chemical tin plating treatment is 60s~80s.
[0012] Optionally, the solar cell is subjected to a first chemical tin plating treatment in an ultrasonic environment using a first chemical tin plating solution; and the solar cell is subjected to a second chemical tin plating treatment using a second chemical tin plating solution, wherein the concentration of stannous ions in the first chemical tin plating solution is less than the concentration of stannous ions in the second chemical tin plating solution.
[0013] Optionally, the concentration of tin sub-ions in the first electroless tin plating solution is 7 g / L to 13 g / L, and the concentration of tin sub-ions in the second electroless tin plating solution is 10 g / L to 20 g / L.
[0014] Optionally, after performing a second chemical tin plating treatment on the solar cell to form a second tin plating layer on top of the first tin plating layer, the method further includes:
[0015] The cleaning fluid is sprayed onto the solar cell while vacuum adsorption is used to remove the cleaning fluid from the surface of the solar cell, thereby performing vacuum cleaning on the solar cell.
[0016] Optionally, the provision of a solar cell includes:
[0017] A copper seed layer is sputtered to form a copper seed layer on the surface of a solar cell substrate, and a photosensitive adhesive layer is formed on the copper seed layer. The non-gateline areas of the photosensitive adhesive layer are printed and exposed.
[0018] The photosensitive adhesive layer is developed to form patterned grooves on the photosensitive adhesive layer, the patterned grooves corresponding to the grid line setting area on the photosensitive adhesive layer;
[0019] The solar cell substrate is subjected to a first electroplating process to reduce the adhesion of the unexposed photosensitive adhesive remaining in the patterned grooves to the surface of the copper seed layer.
[0020] The solar cell substrate is subjected to a second electroplating process to form copper grid lines within the patterned grooves, thereby obtaining the solar cell.
[0021] Optionally, the current density of the first electroplating is 0.5–2.5 A / dm². 2 The first electroplating time is 60-150 seconds.
[0022] Optionally, after the solar cell substrate undergoes the first electroplating, the process further includes:
[0023] The solar cell is immersed in a sodium carbonate solution or potassium carbonate solution with a mass percentage of 2% to 4% for 1 to 5 minutes.
[0024] Secondly, one embodiment of this application provides a solar cell prepared using the solar cell preparation method described above.
[0025] The solar cell fabrication method and solar cell of this application embodiment involve a first chemical tin plating treatment performed at a relatively high temperature. This reduces the viscosity of the chemical tin plating solution, increasing its fluidity and allowing stannous ions to flow more easily to the bottom of the copper grid lines. Simultaneously, the first chemical tin plating treatment is performed in an ultrasonic environment, resulting in a more uniform distribution of stannous ions in the chemical tin plating solution. This further promotes the replenishment of stannous ions at the bottom of the copper grid lines, thus suppressing the galvanic effect at the bottom of the copper grid lines. The first chemical tin plating treatment uniformly covers the surface of the copper grid lines with a first tin plating layer. The second chemical tin plating treatment continues to form a second tin plating layer on top of the first tin plating layer. Since the surface of the copper grid lines is already covered with the first tin plating layer, copper oxidation caused by the galvanic effect will not occur during the second chemical tin plating process. This increases the contact area between the copper grid lines and the surface of the solar cell substrate, improves the grid line adhesion, and ultimately improves the product quality of the solar cell. Attached Figure Description
[0026] Figure 1 This is a schematic flowchart illustrating a method for fabricating a solar cell according to an embodiment of this application.
[0027] Figure 2 for Figure 1 The diagram shows the structure of a solar cell in the fabrication method of the solar cell.
[0028] Figure 3 for Figure 1 The diagram illustrates the principle of the Gabriel effect in the copper grid lines of a solar cell during its fabrication.
[0029] Figure 4 for Figure 1 The diagram shows the chemical tin plating reaction process in the preparation method of the solar cell.
[0030] Figure 5 for Figure 1 The diagram shows a process flow chart for fabricating copper grid lines in the method of preparing a solar cell.
[0031] Figure 6 for Figure 1 Scanning electron microscope image of the patterned grooves obtained by development in the fabrication method of the solar cell shown.
[0032] Figure 7 This is a scanning electron microscope image of the argon ion cross section of the solar cell in Embodiment 1 of this application.
[0033] Figure 8 This is a scanning electron microscope image of the argon-ion cross-section of the solar cell in Comparative Example 1 of this application. Detailed Implementation
[0034] To facilitate understanding of this application, a more complete description will be provided below with reference to the accompanying drawings. Preferred embodiments of this application are shown in the drawings. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of this application.
[0035] It should be noted that when a component is said to be "fixed to" another component, it can be directly attached to the other component or there may be an intervening component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there may be an intervening component.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0037] As used in this article, the description of "a1~a2" means "greater than or equal to a1" and "less than or equal to a2". For example, if x is 0~1, it means: 0≤x≤1.
[0038] like Figures 1 to 8 As shown, this is a method for preparing a solar cell according to one embodiment of this application.
[0039] like Figure 1 As shown, the method for fabricating this solar cell includes the following steps S11 to S13:
[0040] Step S11: Provide a solar cell, which includes a solar cell substrate and copper grid lines disposed on the surface of the solar cell substrate.
[0041] like Figure 2 As shown, the solar cell 100 includes a solar cell substrate 10 and copper grid lines 21, which are bonded to the surface of the solar cell substrate 10 through their bottom 21b.
[0042] Step S12: Perform a first chemical tin plating treatment on the solar cell in an ultrasonic environment to form a first tin plating layer on the surface of the copper grid lines.
[0043] In the first chemical tin plating process, the solar cell 100 is placed in a first tin plating bath containing a first chemical tin plating solution, and the stannous ions Sn in the first chemical tin plating solution... 2+ Stannous ions (Sn) undergo a redox reaction with a reducing agent. 2+ It is reduced to metallic tin (Sn), and the reducing agent is oxidized to form oxidation products.
[0044] On the surface of copper grid line 21, tin ions Sn 2+ First, a substitution reaction is performed on the surface of copper grid line 21 as shown in the following equation: Cu→Cu 2+ +e - Sn 2+ +e - →Sn. Subsequently, the stannous ion Sn 2+ Stannous ions (Sn) undergo a redox reaction with a reducing agent. 2+ It is reduced to metallic tin (Sn) and then continues to deposit.
[0045] like Figure 3 As shown, assuming that the surface of the bottom 21b of the copper gate line 21 is affected by tin subions Sn 2+ If the copper exposed area 21a is not replenished in time, it will act as a "sacrificial anode" and be gradually corroded during the chemical tin plating process, resulting in the Giovanni effect, which causes the bottom 21b to reduce in width due to corrosion.
[0046] The temperature of the first chemical tin plating process is higher than that of the second chemical tin plating process in the subsequent steps. The viscosity of the first chemical tin plating solution, which has a relatively higher temperature, decreases and the fluidity of the first chemical tin plating solution increases. Tin ions are more likely to flow with the liquid to the bottom 21b of the copper grid line 21, so as to suppress the Giovanni effect at the bottom 21b of the copper grid line 21.
[0047] The first chemical tin plating process is performed in an ultrasonic environment. Under the action of ultrasound, the distribution of stannous ions in the first chemical tin plating solution is more uniform, promoting the replenishment of stannous ions to the area where the bottom 21b of the copper grid line 21 is located, thereby suppressing the Giovanni effect at the bottom 21b of the copper grid line 21. At the same time, the tin plating layer can be uniformly covered on the surface of the copper grid line 21. For example, the ultrasonic intensity can be 20Hz to 50Hz.
[0048] Please see Figure 4 As shown, after the first chemical tin plating treatment, a first tin plating layer 221 is formed on the top wall and side wall of the copper grid line 21, and there is no exposed copper area on the copper grid line 21.
[0049] Step S13: Perform a second chemical tin plating process on the solar cell to form a second tin plating layer on the surface of the first tin plating layer.
[0050] Please continue reading. Figure 4 As shown, after the first chemical tin plating treatment, a second chemical tin plating treatment is performed to form a second tin plating layer 222 on the surface of the first tin plating layer 221, so as to form a complete tin protective layer 22.
[0051] In the second chemical tin plating process, since there is no exposed copper area on the copper grid line 21, the Giavani effect is avoided, the temperature of the second chemical tin plating is relatively low, and it does not need to be carried out in an ultrasonic environment.
[0052] The solar cell fabrication method of this embodiment divides the chemical tin plating process into two stages. A first chemical tin plating treatment uniformly covers the surface of the copper grid lines with a first tin layer. A second chemical tin plating treatment further forms a second tin layer on top of the first tin layer. The first chemical tin plating treatment is performed at a relatively high temperature, which reduces the viscosity of the chemical tin plating solution and increases its fluidity, allowing stannous ions to flow more easily to the bottom of the copper grid lines, thus suppressing the galvanic effect at the bottom of the copper grid lines. Simultaneously, the first chemical tin plating treatment is performed in an ultrasonic environment, resulting in a more uniform distribution of stannous ions in the chemical tin plating solution, further promoting the replenishment of stannous ions at the bottom of the copper grid lines, and further suppressing the galvanic effect. Since the surface of the copper grid lines is already covered with the first tin layer after the first chemical tin plating treatment, copper oxidation caused by the galvanic effect will not occur during the second chemical tin plating process. This increases the contact area between the copper grid lines and the solar cell substrate surface, improves the grid line adhesion, and ultimately improves the product quality of the solar cell.
[0053] In one implementation, the time for the first chemical tin plating process is shorter than the time for the second chemical tin plating process, and the thickness of the first tin plating layer 221 is shorter than the thickness of the second tin plating layer 222.
[0054] In one embodiment, the temperature of the first chemical tin plating treatment is 35°C to 45°C, and the time of the first chemical tin plating treatment is 10 seconds to 30 seconds.
[0055] Within this temperature range, the viscosity of the first chemical tin plating solution is low, resulting in good fluidity. This promotes the fluidity and penetration of the first chemical tin plating solution on the copper grid surface, ensuring that the first chemical tin plating solution can more evenly cover all parts of the copper grid. By controlling the first chemical tin plating process within the aforementioned time range, the surface of the copper grid is fully covered with the first tin plating layer.
[0056] In some embodiments, the temperature of the second chemical tin plating treatment is 30°C to 40°C, and the time of the second chemical tin plating treatment is 60s to 80s.
[0057] In this embodiment, by controlling the tin plating temperature within the above-mentioned range, the deposition efficiency is improved; by controlling the tin plating time within the above-mentioned range, the uniformity and good adhesion of the formed coating are ensured.
[0058] In one implementation, the solar cell is subjected to a first chemical tin plating treatment in an ultrasonic environment using a first chemical tin plating solution; the solar cell is subjected to a second chemical tin plating treatment using a second chemical tin plating solution, wherein the concentration of stannous ions in the first chemical tin plating solution is lower than the concentration of stannous ions in the second chemical tin plating solution.
[0059] In this embodiment, the concentration of the first chemical tin plating solution is lower than that of the second chemical tin plating solution, which further reduces the viscosity of the first chemical tin plating solution and promotes the fluidity and penetration of the first chemical tin plating solution on the surface of the copper grid line.
[0060] In some embodiments, the concentration of stannous ions in the first electroless tin plating solution is 7 g / L to 13 g / L, and the concentration of stannous ions in the second electroless tin plating solution is 10 g / L to 20 g / L.
[0061] In this embodiment, the concentration of the first chemical tin plating solution is controlled within the above-mentioned range to promote the fluidity and permeability of the first chemical tin plating solution on the surface of the copper grid line; the concentration of the second chemical tin plating solution is controlled within the above-mentioned range to improve the stability of the chemical reaction, thereby improving the quality of the second tin plating layer.
[0062] For example, the first and second chemical tin plating solutions, in addition to stannous ions, respectively include a reducing agent, a complexing agent, sulfuric acid, and a surfactant. When the concentration of stannous ions in the tin plating solution decreases, the concentrations of the other components also decrease, thus further reducing the viscosity of the low-concentration tin plating solution.
[0063] Specifically, the reducing agent can be, for example, sodium hypophosphite, and thus, during the chemical tin plating process, the following redox reaction occurs: Sn 2+ +NaH2PO2 + H2O → Sn + NaH2PO3 + 2H + Complexing agents, such as thiourea, can coordinate with stannous ions to form complexes, preventing premature deposition of stannous ions and ensuring their full utilization to improve the deposition efficiency of electroless tin plating. Simultaneously, the complex formation by thiourea and stannous ions prevents their oxidation. Sulfuric acid inhibits both the oxidation and hydrolysis of stannous ions, ensuring a sufficiently high sulfuric acid content in the plating solution; for example, the molar ratio of stannous ions to sulfuric acid (H₂SO₄) can be controlled at 1:5. The addition of surfactants can reduce the surface tension of the electroless tin plating solution, promoting its fluidity and penetration on the copper grid surface.
[0064] In one implementation, the following steps are included after step S13:
[0065] Step S14: While spraying the cleaning fluid onto the solar cell, vacuum adsorption is used to remove the cleaning fluid from the surface of the solar cell to perform vacuum cleaning on the solar cell.
[0066] During vacuum cleaning, water is first sprayed onto the surface of the solar cells through nozzles. The water stream should have sufficient pressure to effectively impact and remove residual material from the solar cell surface and the grooves formed between adjacent grid lines. Simultaneously, the water and residue sprayed onto the solar cells are immediately sucked up through a suction head or nozzle connected to the vacuum system. This process prevents water from re-contaminating the cleaned area and quickly removes residue, minimizing water retention time.
[0067] Furthermore, the water jet pressure can be increased, allowing the high-pressure water jet to penetrate deep into the groove and flush away residue adhering to the groove walls. High-pressure jetting is particularly important for small or complex groove structures. Simultaneously, vacuum suction can immediately remove any residue carried away by the water jet, preventing it from redepositing in the groove. This method ensures the cleanliness of the groove's interior, and is especially effective for hard-to-reach areas.
[0068] In this embodiment, vacuum washing can effectively remove any residual electrolyte solution adhering between the grid lines, avoiding corrosion of the grid lines caused by the failure to remove residual electrolyte in time.
[0069] As one implementation method, step S11 specifically includes the following steps:
[0070] Step S111: A copper seed layer is sputtered on the surface of the solar cell substrate, a photosensitive adhesive layer is formed on the copper seed layer, and the non-grid line areas of the photosensitive adhesive layer are printed and exposed.
[0071] For example, please refer to Figure 5 As shown, the solar cell substrate 10 can be a heterojunction with Intrinsic Thin Layer (HJT) solar cell substrate, which includes a silicon wafer substrate 11, a first intrinsic amorphous silicon layer 121 and a second intrinsic amorphous silicon layer 122 respectively stacked on the first surface and the second surface of the silicon wafer substrate 11, an N-type doped amorphous silicon layer 131 stacked on the side of the first intrinsic amorphous silicon layer 121 away from the silicon wafer substrate 11, a P-type doped amorphous silicon layer 132 stacked on the side of the second intrinsic amorphous silicon layer 122 away from the silicon wafer substrate 11, and a deposited transparent conductive film 14 respectively stacked on the side of the N-type doped amorphous silicon layer 131 away from the silicon wafer substrate 11 and on the side of the P-type doped amorphous silicon layer 132 away from the silicon wafer substrate 11. The silicon wafer substrate 11 is a silicon wafer with textured upper and lower surfaces respectively.
[0072] Copper seed layers 211 can be deposited on the two transparent conductive films 14 using PVD magnetron sputtering equipment, respectively. Please refer to [link to relevant documentation]. Figure 5As shown. The thickness of the two copper seed layers 211 can be 60nm to 150nm respectively, and the thicknesses of the two copper seed layers 211 are different.
[0073] Photosensitive adhesive is coated onto two copper seed layers 211 of the solar cell substrate 10 to form a photosensitive adhesive layer on each of the two copper seed layers 211. The photosensitive adhesive layer can be a negative photosensitive adhesive layer. For example, the thickness of the photosensitive adhesive layer can be 10 to 15 μm.
[0074] During the printing exposure process, ultraviolet light emitted by the light source of the printing mechanism passes through a mask and irradiates the photosensitive emulsion layer to transfer the mask pattern onto the photosensitive emulsion layer through printing exposure. Since ultraviolet light cannot penetrate the mask pattern and the mask pattern corresponds to the grid pattern, the pattern transferred onto the photosensitive emulsion layer is the grid pattern. The grid pattern covers the grid setting area of the photosensitive emulsion layer, which is not irradiated by the ultraviolet light of the printing mechanism. The non-grid area is not covered. During exposure, under the action of the light emitted by the light source of the printing mechanism, the monomers in the non-grid area of the photosensitive emulsion layer cross-link to form polymers that are not easily soluble in the developer. The grid area of the photosensitive emulsion layer is not affected by ultraviolet light, and the monomers in the grid area of the photosensitive emulsion layer are easily soluble in the developer and are removed in subsequent steps. The resulting patterned grooves correspond to the grid pattern.
[0075] Step S112: Develop the photosensitive emulsion layer to form patterned grooves on the photosensitive emulsion layer, the patterned grooves corresponding to the grid line setting area on the photosensitive emulsion layer.
[0076] During the development process, the unexposed photosensitive adhesive in the grid line area of the photosensitive adhesive layer is dissolved using a developing solution. The photosensitive adhesive in the grid line area is removed, and patterned grooves are formed in the grid line area of the photosensitive adhesive layer. Specifically, the developing solution can be an alkaline solution, which can be formed by dissolving an alkaline reagent in water, such as a sodium carbonate (Na₂CO₃) solution. Under ultraviolet light, the photosensitive adhesive layer in the first designated area (non-grid line area) undergoes a cross-linking polymerization reaction to form a polymer that is difficult to dissolve in the alkaline solution. In the grid line area, the alkaline-soluble hydrophilic groups in the photosensitive adhesive layer that have not undergone cross-linking polymerization react with the alkaline solution and are dissolved and removed.
[0077] Please see Figure 6 As shown, residual adhesive exists on the bottom wall of the patterned groove, specifically as follows: Figure 6 The residual adhesive shown at point A1 is present in the middle part of the bottom wall, such as Figure 6The residual adhesive at point A2 is present at the edge of the bottom wall in the width direction. The residual adhesive (at point A1) on the bottom wall of the patterned groove is located between the grid lines and the surface of the solar cell substrate, directly affecting the adhesion between the grid lines and the solar cell substrate. At the same time, the residual adhesive at the edge of the bottom wall of the patterned groove (at point A2) narrows the width of the contact area between the electroplated grid lines and the solar cell substrate, reducing the contact area between the grid lines and the solar cell substrate, further affecting the adhesion between the grid lines and the solar cell substrate.
[0078] Step S113: Perform a first electroplating on the solar cell substrate to reduce the adhesion of the unexposed photosensitive adhesive remaining in the patterned grooves to the surface of the solar cell substrate.
[0079] The residual adhesive on the bottom wall of the patterned groove is unexposed photosensitive adhesive, which has poor stability and is easily affected by corrosive reagents or the electric field applied to it. The properties of the unexposed residual adhesive are changed by the first electroplating, thereby reducing the adhesion of the unexposed photosensitive adhesive remaining in the patterned groove to the surface of the copper seed layer.
[0080] The unexposed adhesive residue comprises resin, photosensitizer, and additives. The adhesive residue on the bottom wall of the patterned groove forms a weak chemical bond with the surface of the battery substrate. During the first electroplating process, the electroplating solution comes into contact with the adhesive residue on the bottom wall of the patterned groove. Hydrogen ions and metal ions in the electroplating solution interact with the components in the adhesive residue, changing its chemical properties and weakening the chemical bond between the adhesive residue and the copper seed layer surface. During the first electroplating process, the flow of the electroplating solution and the effect of the electroplating electric field generate shear force on the adhesive residue, reducing its adhesion to the copper seed layer surface. Furthermore, during the first electroplating process, an extremely thin metal layer is electroplated between the adhesive residue and the copper seed layer surface, further reducing the adhesion of the adhesive residue to the copper seed layer surface and making it easier for the adhesive residue to peel off.
[0081] In one implementation method, the current density of the first electroplating is 0.5–2.5 A / dm². 2 The first electroplating time is 60-150 seconds.
[0082] The first electroplating is pre-plating, which mainly removes unexposed residual adhesive. Its current density can be less than or equal to the current density when electroplating the grid lines, and the electroplating time is also shorter.
[0083] Step S114: Perform a second electroplating on the solar cell substrate to form copper grid lines within the patterned grooves, thereby obtaining the solar cell.
[0084] After the first electroplating, the solar cell substrate undergoes copper electroplating in a copper sulfate solution. Please refer to [link to previous section]. Figure 5 As shown, it should be noted that Figure 5The photosensitive emulsion layer is not shown in the diagram. A second electroplating process continues on the copper seed layer 211 to form an electroplated copper layer 212. The copper seed layer 211 and the electroplated copper layer 212 together form the copper grid line 21 in the grid line location region. After the second electroplating, the copper grid line 21 is formed within the patterned groove. Please continue reading thereafter. Figure 5 As shown, in subsequent steps, the photosensitive adhesive layer and the copper seed layer in the non-grid line area are removed to expose the surface of the solar cell substrate 10, while the copper seed layer 211 in the grid line area is retained.
[0085] In this embodiment, the first electroplating removes residual adhesive from the bottom wall of the patterned groove, and the second electroplating leaves no residual adhesive between the copper grid lines and the copper seed layer. This increases the contact area between the grid lines and the surface of the solar cell substrate, improving the grid line adhesion and thus enhancing the product quality of the solar cell. Furthermore, since there are no gaps between the bottom ends of the copper grid lines and the solar cell substrate, the Giovanni effect is less likely to occur during the chemical tin plating process.
[0086] In some embodiments, the following steps are included after step S113 and before step S114:
[0087] Step S113a: Immerse the solar cells in a sodium carbonate solution or potassium carbonate solution with a mass percentage of 2% to 4% for 1 to 5 minutes.
[0088] In this embodiment, after the first electroplating, the residual adhesive is more easily detached from the bottom wall of the patterned groove. At this time, the alkaline soaking solution (sodium carbonate solution or potassium carbonate solution) can fully contact the residual adhesive to dissolve it.
[0089] For example, sodium carbonate, as a moderately strong alkali, can effectively remove photosensitive adhesive without damaging the substrate. Compared to other more alkaline solutions (such as sodium hydroxide, NaOH), sodium carbonate is less corrosive and has less potential damage to the substrate. Sodium carbonate has high solubility in water, and its solution is stable, not easily decomposed or deteriorated, thus maintaining its adhesive removal efficiency for a long time. By changing the concentration and temperature of the sodium carbonate solution, the rate of adhesive removal can be precisely controlled.
[0090] Furthermore, after the alkaline soaking process is completed, it is necessary to rinse with water to remove any residual alkaline soaking solution.
[0091] Example 1
[0092] This embodiment provides a method for fabricating a solar cell, including the following steps:
[0093] Step 1-1: The silicon wafer substrate 11 is texturized and cleaned to form a uniform "positive pyramid" textured surface on its surface. The base dimension (side length of the square base) of the pyramid structure can be 1–10 μm.
[0094] Steps 1-2 involve depositing a first intrinsic amorphous silicon layer 121 and an N-type doped amorphous silicon layer 131 on the upper surface of the texturized silicon substrate 11 using a PECVD (plasma-enhanced chemical vapor deposition) plasma deposition apparatus. Then, a second intrinsic amorphous silicon layer 122 and a P-type doped amorphous silicon layer 132 are sequentially deposited on the lower surface of the texturized silicon substrate 11 using the same PECVD apparatus. The thickness of the first intrinsic amorphous silicon layer 121 can be 2–10 nm, and the thickness of the second intrinsic amorphous silicon layer 122 can be 2–14 nm; the thickness of the N-type doped amorphous silicon layer 131 can be 3–30 nm, and the thickness of the P-type doped amorphous silicon layer 132 can be 3–30 nm.
[0095] Steps 1-3 involve using PVD (Physical Vapor Deposition) magnetron sputtering to deposit transparent conductive films 14 on both the N-type doped amorphous silicon layer 131 and the P-type doped amorphous silicon layer 132. Each of the two transparent conductive films 14 can be a TCO conductive film. The thickness of each transparent conductive film 14 can be 50–110 nm.
[0096] Steps 1-4 involve depositing copper seed layers on two transparent conductive films 14 using a PVD magnetron sputtering apparatus. The thicknesses of the two copper seed layers can be 50–250 nm, respectively.
[0097] Steps 1-5, Coating: Photosensitive adhesive is coated on the surfaces of the two copper seed layers of the solar cell substrate, and the thickness of the photosensitive adhesive layer is controlled between 5 and 15 μm.
[0098] Steps 1-6, Printing and Exposure: Print the designed grid pattern onto the photosensitive emulsion layer and expose it. During this process, the photosensitive emulsion layer undergoes a change in color upon exposure (non-grid area is exposed), distinguishing it from the unexposed areas (i.e., the grid area). The distance between the photosensitive emulsion layer and the mask is 70 μm, and the exposure energy is 135 mJ / cm². 2 The exposure time is 500ms.
[0099] Steps 1-7, Development: The unexposed photosensitive emulsion layer (raster area) is cleaned and removed using a sodium carbonate (Na2CO3) solution. The sodium carbonate concentration is controlled at 10-20 g / L, the solution temperature is 25℃-40℃, the nozzle pressure is 0.5 bar-2.5 bar, and the solution pH is controlled between 8 and 12. The sodium carbonate solution reacts with the unexposed photosensitive emulsion layer to form patterned grooves.
[0100] Steps 1-8, Edge binding: Wrap the four corner edges and corner positions with edge binding adhesive. The width of the edge binding adhesive is greater than or equal to 50μm and less than or equal to 1mm, and the thickness of the edge binding adhesive is 2-15μm.
[0101] Steps 1-9, First Electroplating: Pre-plating is performed in a copper sulfate electroplating solution, wherein the concentration of H2SO4 in the copper sulfate electroplating solution is 100 g / L, and Cu... 2+ The concentration was 50 g / L, the current density was 2.0 ASD, and the electroplating time was 60 seconds.
[0102] Steps 1-10, Second electroplating: Electroplating copper grid lines in a copper sulfate electroplating solution, with the height of the copper grid lines controlled between 5 and 18 μm.
[0103] Steps 1-11, Re-etching: Remove all the edge-sealing adhesive and photosensitive adhesive layers in a strongly alkaline solution; use a re-etching solution to perform a re-etching cleaning process on the solar cell to remove the metal seed layer in the non-grid area of the solar cell.
[0104] Steps 1-12, light injection: The battery substrate after film removal and re-etching is subjected to light injection treatment at a temperature of 200℃~230℃ for 40s~100s.
[0105] Steps 1-13: First chemical tin plating. Place the solar cell in the first chemical tin plating solution, turn on the ultrasonic treatment (ultrasonic intensity of 40Hz), and perform the first chemical tin plating treatment for 25s at 42℃. The concentration of tin subions in the first chemical tin plating solution is 7g / L~13g / L.
[0106] Steps 1-14: Second chemical tin plating. The solar cell is placed in the second chemical tin plating solution and treated at 32°C for 75 seconds. The concentration of stannous ions in the second chemical tin plating solution is 10 g / L to 20 g / L.
[0107] Steps 1-15: Vacuum washing. While spraying cleaning fluid onto the solar cell, vacuum adsorption is used to remove the cleaning fluid from the surface of the solar cell, thus performing vacuum cleaning on the solar cell.
[0108] Comparative Example 1
[0109] This embodiment provides a method for fabricating a solar cell, including the following steps:
[0110] Step 2-1: The silicon wafer substrate 11 is texturized and cleaned to form a uniform "positive pyramid" textured surface on its surface. The base dimension (side length of the square base) of the pyramid structure can be 1–10 μm.
[0111] Step 2-2: Using PECVD (plasma-enhanced chemical vapor deposition) equipment, a first intrinsic amorphous silicon layer 121 and an N-type doped amorphous silicon layer 131 are deposited on the upper surface of the texturized silicon wafer substrate 11, respectively. Then, using the same PECVD equipment, a second intrinsic amorphous silicon layer 122 and a P-type doped amorphous silicon layer 132 are deposited sequentially on the lower surface of the texturized silicon wafer substrate 11. The thickness of the first intrinsic amorphous silicon layer 121 can be 2–10 nm, and the thickness of the second intrinsic amorphous silicon layer 122 can be 2–14 nm; the thickness of the N-type doped amorphous silicon layer 131 can be 3–30 nm, and the thickness of the P-type doped amorphous silicon layer 132 can be 3–30 nm.
[0112] Steps 2-3 involve using PVD (Physical Vapor Deposition) magnetron sputtering to deposit transparent conductive films 14 on both the N-type doped amorphous silicon layer 131 and the P-type doped amorphous silicon layer 132. Each of the two transparent conductive films 14 can be a TCO conductive film. The thickness of each transparent conductive film 14 can be 50–110 nm.
[0113] Steps 2-4 involve depositing copper seed layers on two transparent conductive films 14 using a PVD magnetron sputtering apparatus. The thicknesses of the two copper seed layers can be 50–250 nm, respectively.
[0114] Steps 2-5, Coating: Photosensitive adhesive is coated on the surfaces of the two copper seed layers of the solar cell substrate, and the thickness of the photosensitive adhesive layer is controlled between 5 and 15 μm.
[0115] Steps 2-6, Printing and Exposure: Print the designed grid pattern onto the photosensitive emulsion layer and expose it. During this process, the photosensitive emulsion layer undergoes a change in color upon exposure (non-grid area is exposed), distinguishing it from the unexposed areas (i.e., the grid area). The distance between the photosensitive emulsion layer and the mask is 70 μm, and the exposure energy is 135 mJ / cm². 2 The exposure time is 500ms.
[0116] Steps 2-7, Development: The unexposed photosensitive emulsion layer (raster area) is cleaned and removed using a sodium carbonate (Na2CO3) solution. The sodium carbonate concentration is controlled at 10-20 g / L, the solution temperature is 25℃-40℃, the nozzle pressure is 0.5 bar-2.5 bar, and the solution pH is controlled between 8 and 12. The sodium carbonate solution reacts with the unexposed photosensitive emulsion layer to form patterned grooves.
[0117] Steps 2-8, Edge binding: Wrap the four corner edges and corner positions with edge binding adhesive. The width of the edge binding adhesive is greater than or equal to 50μm and less than or equal to 1mm, and the thickness of the edge binding adhesive is 2-15μm.
[0118] Steps 2-9, electroplating: Electroplating copper grid lines in a copper sulfate electroplating solution, with the height of the copper grid lines controlled between 4 and 15 μm.
[0119] Step 2-10, Film Removal and Re-etching: Remove all the edge-sealing adhesive and photosensitive adhesive layers in a strongly alkaline solution; use a re-etching solution to perform a re-etching cleaning process on the solar cell to remove the metal seed layer in the non-grid area of the solar cell.
[0120] Step 2-11, light injection: The battery substrate after film removal and re-etching is subjected to light injection treatment at a temperature of 200℃~230℃ for 40s~100s.
[0121] Step 2-12, chemical tin plating: The light-injected wafer is immersed in a tin plating solution to form a 100-200nm thick layer of pure tin covering the surface of the copper grid lines.
[0122] Steps 2-13, vacuum water washing: while spraying cleaning fluid onto the solar cell, vacuum adsorption is used to remove the cleaning fluid from the surface of the solar cell, so as to perform vacuum cleaning on the solar cell.
[0123] The argon ion cross-sections of the solar cells obtained in Example 1 and Comparative Example 1 were measured using scanning electron microscopy (SEM). The test results are shown in [link to SEM]. Figure 7 and Figure 8 As shown.
[0124] Please see Figure 7 As shown, after chemical tin plating, the copper grid lines of the solar cell prepared in Example 1 are tightly bonded to the copper seed layer at both ends of the bottom of the copper grid lines without any gaps. At the same time, the edge of the bottom wall of the copper grid lines is tightly bonded to the copper seed layer, and the middle part of the bottom wall of the copper grid lines is tightly bonded to the copper seed layer.
[0125] Please see Figure 8As shown, after chemical tin plating, there is a large gap between the two ends of the bottom of the copper grid line and the copper seed layer in the solar cell prepared in Comparative Example 1, which reduces the contact area between the bottom of the copper grid line and the copper seed layer.
[0126] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0127] The above embodiments merely illustrate preferred implementations of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. Therefore, the scope of protection of this patent application should be determined by the appended claims.
Claims
1. A method for fabricating a solar cell, characterized in that, include: A solar cell is provided, the solar cell including a solar cell substrate and copper grid lines disposed on the surface of the solar cell substrate; The solar cell is subjected to a first chemical tin plating treatment in an ultrasonic environment to form a first tin plating layer on the surface of the copper grid lines; The solar cell is subjected to a second chemical tin plating treatment to form a second tin plating layer on the surface of the first tin plating layer; The temperature of the first chemical tin plating treatment is higher than the temperature of the second chemical tin plating treatment.
2. The method for preparing a solar cell according to claim 1, characterized in that, The temperature of the first chemical tin plating treatment is 35℃~45℃, and the time of the first chemical tin plating treatment is 10s~30s.
3. The method for preparing a solar cell according to claim 2, characterized in that, The temperature of the second chemical tin plating treatment is 30℃~40℃, and the time of the second chemical tin plating treatment is 60s~80s.
4. The method for preparing a solar cell according to claim 1, characterized in that, The solar cell is subjected to a first chemical tin plating treatment in an ultrasonic environment using a first chemical tin plating solution; the solar cell is subjected to a second chemical tin plating treatment using a second chemical tin plating solution, wherein the concentration of stannous ions in the first chemical tin plating solution is less than the concentration of stannous ions in the second chemical tin plating solution.
5. The method for preparing a solar cell according to claim 4, characterized in that, The concentration of stannous ions in the first electroless tin plating solution is 7 g / L to 13 g / L, and the concentration of stannous ions in the second electroless tin plating solution is 10 g / L to 20 g / L.
6. The method for preparing a solar cell according to claim 1, characterized in that, After performing a second chemical tin plating treatment on the solar cell to form a second tin plating layer on top of the first tin plating layer, the process further includes: The cleaning fluid is sprayed onto the solar cell while vacuum adsorption is used to remove the cleaning fluid from the surface of the solar cell, thereby performing vacuum cleaning on the solar cell.
7. The method for preparing a solar cell according to claim 1, characterized in that, The provision of a solar cell includes: A copper seed layer is sputtered to form a copper seed layer on the surface of a solar cell substrate, and a photosensitive adhesive layer is formed on the copper seed layer. The non-gateline areas of the photosensitive adhesive layer are printed and exposed. The photosensitive adhesive layer is developed to form patterned grooves on the photosensitive adhesive layer, the patterned grooves corresponding to the grid line setting area on the photosensitive adhesive layer; The solar cell substrate is subjected to a first electroplating process to reduce the adhesion of the unexposed photosensitive adhesive remaining in the patterned grooves to the surface of the copper seed layer. The solar cell substrate is subjected to a second electroplating process to form copper grid lines within the patterned grooves, thereby obtaining the solar cell.
8. The method for preparing a solar cell according to claim 7, characterized in that, The current density for the first electroplating is 0.5–2.5 A / dm². 2 The first electroplating time is 60-150 seconds.
9. The method for preparing a solar cell according to claim 7, characterized in that, After the solar cell substrate undergoes the first electroplating, the process further includes: The solar cell is immersed in a sodium carbonate solution or potassium carbonate solution with a mass percentage of 2% to 4% for 1 to 5 minutes.
10. A solar cell, characterized in that, The solar cell is prepared using the method described in any one of claims 1 to 9.